FEATURES OF THE IMPACT OF ORGANIZATIONAL CULTURE ON THE INDUSTRIAL ENTERPRISES EFFICIENCY - D. Shkolnyi; I. Groshev (Вестник университета)
Organizational culture is an attribute of any company. Manufacturing enterprises are most affected by it. The quality of organizational culture affects the efficiency of all production processes. To achieve the best results, it is necessary to work on optimizing the company’s culture. The functions of the organizational culture, its type, the nature of the interaction between employee and organizational elements have been considered and the estimated components of the efficiency of the organizational culture have been identified. The ideology of a competitive product of an industrial enterprise in the future has been considered conceptually.